An Introduction to Network Programming with Java Java 7 Compatible - Graba, Jan (Springer London : Imprint: Springer, 2013)
Since the second edition of this text, the use of the Internet and networks generally has continued to expand at a phenomenal rate. This has led to both an increase in demand for network software and to improvements in the technology used to run such networks, with the latter naturally leading to changes in the former. During this time, the Java libraries have been updated to keep up with the new developments in network technology, so that the Java programming language continues to be one of the mainstays of network software development. In providing a very readable text that avoids getting immersed in low-level technical details, while still providing a useful, practical guide to network programming for both undergraduates and busy IT professionals, this third edition continues the trend of its predecessors. To retain its currency, the text has been updated to reflect changes that have taken place in Java's network technology over the past seven years (including the release of Java 7), whilst retaining its notable features of numerous code examples, screenshots and end-of-chapter exercises.